Clinical and Renal Histology Findings and Different Responses to Induction Treatment Affecting the Long-Term Renal Outcomes of Children With ANCA-Associated Vasculitis: a Single-Center Cohort Analysis - Yang, Jing; Yang, Yuan; Xu, Yongli; Zhou, Lanqi; Zhou, Luowen; Yin, Xiaoling; Pu, Jinyun; Yang, Fengjie; Liu, Yaping; He, Yonghua; Chen, Yaxian; Yuan, Huiqing; et al. (Frontiers in Immunology, 2022)
Introduction Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is relatively rare in children. This article aimed to analyze clinical and renal histology findings and different responses to induction treatment associated with the long-term renal outcomes in children with AAV in a single center. Methods All pediatric patients with AAV admitted to Tongji Hospital from January 2002 to January 2021 were included in the study. The demographic, clinical, pathological, laboratory, and treatment data and outcomes were collected and analyzed to identify predictors associated with response to induction treatment and progression to end-stage renal disease (ESRD). Results In total, 48 children with AAV were included in this cohort; 81.25% of them were women, and 91.7% were microscopic polyangiitis (MPA). Kidney involvement was found in 45 patients (93.75%). The most common histopathological subtype was crescentic form in this cohort according to Berden’s classification. In total, 34 patients (70.8%) showed eGFR <60 ml/min/1.73 m2 at the time of diagnosis. Complete and partial remission was achieved in 8 patients (16.7%) and 19 patients (39.6%), respectively, following 6-month induction treatment. Half of the patients eventually progressed to ESRD at a mean time of (13.04 ± 15.83) months after diagnosis. The independent predictors of nonremission following induction treatment and progression to ESRD were baseline eGFR <60 ml/min/1.73 m2 and hypertension at diagnosis. Renal survival significantly decreased over time in patients with renal sclerotic subtypes or those with nonremission following induction treatment by Kaplan–Meier curve estimation. Conclusions Our study demonstrates that women, MPA, and crescentic subtypes are predominant in pediatric AAV in China. Initial renal failure (eGFR <60 ml/min/1.73 m2), hypertension, sclerotic pathological subtype, and nonremission following induction treatment are predictive of long-term renal outcomes.